An Overview of Chinese Pangolin (Manis pentadactyla): Its General Biology, Status, Distribution and Conservation Threats in Nepal - Thapa, Prakash (The Initiation, 2014)
Chinese Pangolin is nocturnal, shy, non-aggressive, solitary, strange and burrowing mammal which has received low scientific attention. Little information is known about its biology, distribution and status. In Nepal it is distributed in many districts and protected areas. The status of this mammal is decreasing in the country but there is no any research regarding its biology, status and distribution. Although, this mammal is protected nationally and internationally, it is facing too much problems due to habitat destruction and illegal trade. This article mainly focuses on the biology, status, distribution and conservation threats of this ecologically beneficial handsome creature. DOI: http://dx.doi.org/10.3126/init.v5i0.10267 The Initiation 2013 Vol.5; 164-170